Le zone morte dell’arte Un percorso: dalla dolce rêverie al perturbante (Materiali di Estetica. Terza serie, 2024)
The essay explores areas of suspension and emptiness in the aesthetic experience, navigating between the perspective of Mikel Dufrenne and Jean-François Lyotard. Starting with the gentle reconciliation described by Dufrenne, in which the complete reconciliation between subject and world is assumed, we will move on to what breaks this unity. The uncanny, the disorientation, which art presupposes and which a reconciliatory perspective does not presuppose, are for Lyotard those “dead zones” in which vital energies circulate freely. In this passage between rêverie and the uncanny, an attempt will be made to show how art can exist in a state of tension that places the subject before his perceptive and interpretative limits.
Keywords: Uncanny (Das Unheimliche); daydream (rêverie); reversal; Connaturality